An alternative take on AC research and practice: Task-based Assessment Centres - Jackson, Duncan; Mohd Hanafiah, Ahmad; Grace, Gary; Yoon, Jeeyun (Taylor & Francis, 2011)
In chapter 3, Jackson, Ahmad, Grace and Yoon describe task-based assessment centres (TBACs), which adopt a different approach to research and practice of the AC method by focusing on the task list and roles within exercise, rather than dimensions across exercises. although TBACs are designed in much the same way as traditional dimensions-based assessment centres (DBACs), the author argue that performance on the tasks is as important (if not more so) than performance on the dimensions, The authors' claims are supported buy a case study describing a TBAC employed within a New Zealand-based organization and some futher examples of similar practices employed in South Koreea.